Planck Time and the Chemical Soup: The Quantum and Metaphysical Limits of Imitating Consciousness in Machines - Tarlacı, Sultan (Journal of NeuroPhilosophy, 2025)
The boundaries of machine consciousness lie at the intersection of physics, biology, and metaphysics. Although computational power advances rapidly, it remains constrained by the fundamental laws of the universe. Jack Ng (2000) demonstrated that the product of processing speed and stored information is limited by Planck time—the smallest measurable unit of time (≈10⁻⁴³ s)—establishing an ultimate ceiling for information processing. These physical limits suggest that no artificial system can transcend the quantum–gravitational constraints inherent to reality. In contrast, the human brain functions as a dynamic biochemical and electrical system—a “chemical soup” of neurotransmitters, receptors, and ion channels generating subjective awareness. Yet, how consciousness and selfhood emerge from this biological complexity remains unresolved. This study contrasts dualistic and monistic interpretations of consciousness. Dualism posits a metaphysical “essence” beyond material explanation, implying that true artificial consciousness is unattainable. Monism views consciousness as an emergent property of neural information dynamics, potentially reproducible in machines. Ultimately, while machines may simulate awareness, they cannot replicate the quantum–metaphysical foundation of human consciousness. Thus, the final word on artificial consciousness remains unspoken—bounded by both physics and philosophy.